Implementation of Fast Convolution using Robust Vedic Multiplier of Radix-2 - Paradhasaradhi, Damarla; Haridhar, Bharinala; V. Sreekanth Reddy, A; Sri Charan, Dudipalli; Lekhaz, Atyam (International Journal of Engineering and Technology, 2018)
Convolution is an algorithm which is mainly used in video, audio and image processing. Convolution calculation is simple in steps however it consumes a lot of memory as well as power in the computational process. It is a mathematical algorithm which is also used in the applications like filtering, edge detection, de-noising, compression etc., as it can be exploit computational power. In this paper, we implemented the speed of discrete linear convolution using robust Vedic multiplier which is one of the fastest multipliers with two finite-length sequences. By implementing convolution with Vedic multiplier power, area and delay are reduced. This implementation process can be realized by simplifying the convolution building block.Â Â
Keywords: Convolution; De-Noising; Edge Detection; Full Adder; Robust Vedic Multiplier.